Limitations of a Commercial Assay as Diagnostic Test of Autoimmune Encephalitis - Ruiz-García, Raquel; Muñoz-Sánchez, Guillermo; Naranjo, Laura; Guasp, Mar; Sabater, Lidia; Saiz, Albert; Dalmau, Josep; Graus, Francesc; Martinez-Hernandez, Eugenia (Frontiers in Immunology, 2021)
Detection of neuronal surface antibodies (NSAb) is important for the diagnosis of autoimmune encephalitis (AE). Although most clinical laboratories use a commercial diagnostic kit (Euroimmun, Lübeck, Germany) based on indirect immunofluorescence on transfected-cells (IIFA), clinical experience suggests diagnostic limitations. Here, we assessed the performance of the commercial IIFA in serum and CSF samples of patients with suspected AE previously examined by rat-brain immunohistochemistry (Cohort A). Of 6213 samples, 404 (6.5%) showed brain immunostaining suggestive of NSAb: 163 (40%) were positive by commercial IIFA and 241 (60%) were negative. When these 241 samples were re-assessed with in-house IIFA, 42 (18%) were positive: 21 (9%) had NSAb against antigens not included in the commercial IIFA and the other 21 (9%) had NSAb against antigens included in the commercial kit (false-negative results). False-negative results occurred more frequently with CSF (29% vs 10% in serum) and predominantly affected GABABR (39%), LGI1 (17%) and AMPAR (11%) antibodies. Results were reproduced in a separate cohort (B) of 54 AE patients with LGI1, GABABR or AMPAR antibodies in CSF which were missed in 30% by commercial IIFA. Patients with discordant GABABR antibody results (positive in-house but negative commercial IIFA) were less likely to develop full-blown clinical syndrome; no significant clinical differences were noted for the other antibodies. Overall, NSAb testing by commercial IIFA led to false-negative results in a substantial number of patients, mainly those with anti-LG1, GABABR or AMPAR encephalitis. If these disorders are suspected and commercial IIFA is negative, more comprehensive antibody studies are recommended.